Lifetime Allergy Symptoms in IgG4-Related Disease: A Case-Control Study - Sanders, Samantha (Arthritis Care Res (Hoboken), 2022)
OBJECTIVE: The etiology of IgG4-related disease (IgG4-RD) is unknown and there has been controversy over the significance of allergic conditions in IgG4-RD. We examined the prevalence of lifetime allergy symptoms in IgG4-RD and the association between these and IgG4-RD. METHODS: We identified IgG4-RD patients and non-IgG4-RD controls without autoimmune conditions seen at a single center. IgG4-RD patients were classified using the ACR/EULAR classification criteria. Allergy symptoms were ascertained by questionnaire. We assessed the association of IgG4-RD features with allergy symptoms. We compared the proportion of cases and controls with allergy symptoms using conditional logistic regression to estimate odds ratios (OR) and 95% confidence intervals (CI) after matching cases and controls 1:1 by age and sex. RESULTS: Lifetime allergy symptoms were reported by 165 (71%) of 231 IgG4-RD cases. Aero-allergen symptoms were most commonly reported (135, 58%) followed by skin allergy symptoms (97, 42%) and food allergy symptoms (47, 20%). IgG4-RD cases with a history of allergy symptoms were more likely to have head and neck involvement (OR 2.0 [95% CI: 1.1–3.6]) and peripheral eosinophilia (OR 3.3 [95% CI: 1.2–9.0]) than those without allergy symptoms. The prevalence of any allergy symptoms was similar between cases and controls (OR 0.7 [95% CI: 0.4–1.1]); this remained consistent after stratifying by head and neck involvement. CONCLUSION: Lifetime allergy symptoms are common in IgG4-RD but are not reported more often in IgG4-RD compared to non-IgG4-RD patients without autoimmune conditions. These findings suggest that allergies are not uniquely associated with the pathogenesis or presentation of IgG4-RD.